IMPLEMENTASI NILAI KESAMAAN HAK DAN KESAMAAN DERAJAT (ISSUE GENDER) DALAM MENINGKATKAN KEHARMONISAN HIDUP BERMASYARAKAT, BERBANGSA DAN BERNEGARA (Tinjauan historis, sosiologis, politis, ekonomis dan manajemen negara) - Munawar Sadali (Jurnal Terapung : Ilmu - Ilmu Sosial, 2021)
This research is a form of library research with the title "Implementation of the Value of Equality of Rights and Equality of Degrees (Gender Issue) can Increase Harmony in Community, National and State Life (Historical, Sociological, Political, Economic and State Management Reviews) which was carried out. with the aim of meeting the needs of social life so that social inequalities do not occur in educational matters.The subjects in this study of course include the community itself, of course, research is carried out in order to obtain equal rights and degrees as social beings so that there is no difference between men and women.Keywords: Value of Equal Rights and Equal Degrees, Harmony of Life.